A Disabled Lord? Continuity and Legibility in the Resurrection - Clark-Howard, Andrew (Journal of disability & religion, 2026)
Within the diverse field of Christian disability theology, a particular reading of the resurrected body of Jesus Christ as a disabled body—one which continues to bear the ongoing wounds of the crucifixion even in its glorified state—can be observed. Such a position, often supported by both exegetical interpretations of witnesses to the resurrected Jesus, is undergirded by assumptions about both the continuity and legibility of resurrected, eschatological life. Such readings of a “disabled Lord” are thus employed to promote a fuller understanding of the dignity and personhood of people with disabilities. This paper draws on the queer theology of Linn Tonstad to argue that such assumptions are misplaced. The danger with such approaches to disability and the resurrection is that they repeat logics of continuity and legibility which entrench rather than disrupt continuums of dis/ability and personhood. Drawing off antisocial and nonnormative forms of queer theologizing employed by Tonstad and others, this article instead seeks to attend to the inherent instability and fragility of Christian hopes for the future. I therefore argue that disability theology can be better served by nonlinear, noncontinuous accounts of Christian resurrection.